Arbor City Community Foundation. (A), The foundation - Schmedders, Karl, (SAGE knowledge. Cases., 2016)
The Arbor City Community Foundation (ACCF) was a medium-sized endowment established in Illinois in the late 1970s through the hard work of several local families. The vision of the ACCF was to be a comprehensive centre for philanthropy in the greater Arbor City region. This study examines the strategies and returns of the ACCF.